Adult reflection in a graduate-level online distance education course. Issue 1 (2nd January 2016) - York, Cindy S.; Yamagata-Lynch, Lisa C.; Smaldino, Sharon E.
Abstract: This study examined adult learners' ability to engage in critical reflection concerning their own learning in a graduate-level online instructional technology course. The online course was facilitated through asynchronous discussions, and the course topic was about the design and delivery of distance education. The data for this study consisted of four critical reflection papers about students' perception of their learning. The Periodic Reflection Tool, based on activity systems analysis, was introduced to participants as a guide for engaging in in-depth reflection about their learning process and completing their course assignment. After course completion and during data analysis, we applied instrumental learning and communicative learning theories to evaluate how participants used the tool to reflect on their personal learning in the course. At the conclusion of an analysis of their reflection statements, it was found that purposeful reflections guided by the Periodic Reflection Tool could help guide adult learners to reflect on many aspects of their learning and we suggest that the tool could be used to examine adults' transition from traditional to online settings.